The process of creating autonomous regions and metropolitan districts in Ecuador - Pérez Zúñiga. , José María (Revista Universidad de Guayaquil, 2013)
The Constitution of the Republic of Ecuador, 2008 constitutes the first initiative of the Central Government to approach a unique project for structuring the Ecuadorian State. It is an open process, which includes as main innovation, the creation of autonomous regions and metropolitan districts. But its regulation in the Constitution and the Organic Law on Territorial Organization presents constitutional doubts, mainly as far as the regionalization law and the statutes of the autonomous regions and metropolitan districts are concerned, they should be organic laws expressly approve by the National Assembly, since they affect the territorial organization of the state. The deadline for its creation is an exhaustive eight-year period, under constitutional dictation.
Keywords: constitution; organic code of territorial organization; organic law; statute; autonomous regions; metropolitan districts; territorial organization